Exploring Client Preferences for Psychological Counselors in a Chinese Online Health Community: Longitudinal Study - Xiandong Feng; Yinhuan Hu; Holger Pfaff; Sha Liu; Jinzhu Xie; Zemiao Zhang (JMIR Publications, 2024)
BackgroundAlthough online health communities are acknowledged for their role in bridging the supply-demand gap in mental health services, the client decision-making process in these environments remains underexplored. ObjectiveThis study aimed to explore the impact of different signals presented on psychological counselors' home pages on clients' choices. MethodsAdopting signaling theory as the framework, this study classified information into online and offline signals and developed a theoretical model to examine client choice behaviors. We collected data from 487 psychological counselors in a leading Chinese online mental health community during March, June, September, and December 2023. Based on these data, we constructed a 4-period balanced panel dataset. A fixed effects model was used to analyze which signals influence clients' choices of psychological counselors. ResultsRegarding online signals, the service price (β=0.186, P<.001) and online reputation (β=0.489, P=.002) of psychological counselors positively influence clients' choices. Concerning offline signals, psychological counselors' practical experience (β=0.007, P<.001) is positively related to clients' choices. Moreover, the results indicate that the relationship between a counselor's prosocial behavior and clients' choices is not linear but rather exhibits an inverted U-shape. ConclusionsThis study reveals that the varied information provided by psychological counselors has distinct impacts on clients' choices in online health communities. It broadens the application of signaling theory to online behaviors and emphasizes the importance of both online and offline signals. These insights offer strategic guidance for counselors and online platforms to better meet potential clients' needs by optimizing the information presented on psychological counselors' home pages.